2017
DOI: 10.1021/acs.jpca.7b01986
|View full text |Cite
|
Sign up to set email alerts
|

Three-Body Fragmentation from Single Ionization of Water by Electron Impact: The Role of Satellite States

Abstract: Ionization of water with energy transfers close to the 2a inner valence orbital is accompanied by a fast electronic rearrangement driven by electron relaxation and electron-electron correlations. Quasi-degenerate single vacancy and satellites one-electron-two-vacancies excited states in outer shells are created and leave their fingerprints in the three-body fragmentation pattern. Single vacancy states have been associated with Auger decay and double ionization. Satellite excited states are here convincingly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…They have also derived an upper limit for oxygen atom kinetic energy of 1 eV, or 12,000 K. Experiments by Frémont et al (2005) have shown the same hydrogen peak at 0.2 eV as Makarov et al (2004), with the addition of the observation of a population of oxygen atoms at 0.15 eV (or 1740 K) that appears starting from 20 eV electron energy. More recently, Ferreira et al (2017) studied the kinetic energy distribution of oxygen fragments originating from the electron impact dissociation of water, yielding an average O + energy of 0.063 eV (or 731 K) at 30 eV collision energy.…”
Section: Desorption Processes Related To Molecularmentioning
confidence: 99%
“…They have also derived an upper limit for oxygen atom kinetic energy of 1 eV, or 12,000 K. Experiments by Frémont et al (2005) have shown the same hydrogen peak at 0.2 eV as Makarov et al (2004), with the addition of the observation of a population of oxygen atoms at 0.15 eV (or 1740 K) that appears starting from 20 eV electron energy. More recently, Ferreira et al (2017) studied the kinetic energy distribution of oxygen fragments originating from the electron impact dissociation of water, yielding an average O + energy of 0.063 eV (or 731 K) at 30 eV collision energy.…”
Section: Desorption Processes Related To Molecularmentioning
confidence: 99%
“…Also, in Fig. 6, we compare, for a = 1751, the ab initio nonadiabatic couplings (symbols) with the values of the derivatives (solid lines) of the transformation angle g XC [see eqn (2)] obtained with the fitted model (17) and (18), for a few values of y (those corresponding to the dotted lines of Fig. 5).…”
Section: Regularization Of the Conical Intersectionsmentioning
confidence: 99%
“…Experiments of ref. [15][16][17] have measured the kinetic energy release distributions of the fragments formed after electron impact on water molecules, which shed light on the possible routes leading to the different fragmentation schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation